Efeito de diferentes estratégias de irrigação sob a cultura da soja (Glycine max (L.) Merril) na região de Santiago, RS - Gomes, Ana Carla dos Santos (2007)
Among the different production s factors, water is what most limits the productivity of the cultivated plants, especially in regions where the irregular distribution of pluvial precipitation is present. In these cases, the supplemental irrigation is one of the major devices, which is capable of maximizing production, appeasing a larger number of crops throughout the year. The present work had as purpose to evaluate the behavior of soybean culture, acquiring growth, development and production parameters under different irrigation strategies, and to verify which strategy has a better result when larger productivity is concerned. The experiment was conducted in an experimental area at Fazenda Liberdade, located in the municipal district of Santiago RS, in the agricultural year of 2005/2006. The soybean cultivars 8100 and Anta were used in this experiment. The irrigation handling was based on a watering shift settled beforehand among a 7-day recess. The irrigation blades that were applied alongside the cultivation vital cycle were based on the evapotranspiration data measured in an evaporimetric Mini- Tank, being of 60%, 80%, 100% and 120% of the reference evapotranspiration value (ETo). The growth and development parameters were measured, such as, the leaf area index (LAI) and the plants heights in fortnightly periods; and the covered surface in every ten days. The productivity components were determined in the harvest. It was also verified the efficiency of the water usage (USA). The results were submitted to variation analysis and the F test in a 5% error probability level. The average results were compared among themselves using the Tuckey Test in a 5% error probability level. The results showed that no statistically significant differences occurred in the growth and development parameters for both cultivars; there were statistically significant differences with most of the productivity components of the Anta cultivar; as for the 8100 cultivar, the differences were less evident. The cultivars submitted to the ETo s 60% irrigation strategy presented a bigger leaf expansion. They presented a LAI superior to the Brazilian soybean manures. The largest grain production for the 8100 cultivar was obtained under the irrigation strategy of 60%; as for the Anta cultivar, it occurred under the irrigation strategy of 80%. Both types presented bigger values in the USA under the irrigation strategy of 80%. The use of additional irrigation in the soybean cultivation increases the grain productivity in the westborder region in the state of Rio Grande do Sul, for the conditions, considered characteristics of the period and factors.